Propuesta de un sistema de potabilización de agua subterránea para la finca las brisas en Nemocón, Cundinamarca (2019)
This project presents a proposal for a groundwater potabilization system for the Las Brisas farm, because the supply of potable water is insufficient and inconsistent, generating delays and losses in the productive processes of the farm. The physicochemical, microbiological, and tributary properties are determined, and so on, the parameters that are respected with respect to resolution 2115 of 2007 for water quality for human consumption, based on these results, a bibliographic search of employee treatment systems for the purification of waters through a selection matrix. The aeration, the coagulation, the flocculation, the sedimentation, the ablation, the disinfection and the neutralization are the stages that are carried out in an experimental end with the fine conditions of operation of the system, where it is concluded that for the coagulation it is used ferric chloride (FeCl3), in flocculation Lipesa 1569A, in the disinfection of calcium hypochlorite (Ca (CIO) 2) and in the neutralization of calcium hydroxide (Ca (OH) 2). After the experimental development. Finally, we carry out a financial analysis of the proposed system, evaluating the costs of the proposal, the financial viability and the benefits for the farm if the proposal is implemented.